Evaluation of phenol treatment for pilonidal sinus in adolescents - Kılıç, Ayten Başak; Muti Acar, Merve Nur; Kılıç, Sinan; Ekingen, Gülşen (Frontiers in Pediatrics, 2025)
ObjectivePilonidal sinus disease (PSD) is chronic condition predominantly affecting adolescents, often associated with risk factors such as obesity, poor hygiene, and prolonged sitting. Minimally invasive treatments like phenol procedure have gained attention as alternatives to traditional surgical methods due to their simplicity and potential for shorter recovery. This study aims to evaluate the efficacy and safety of phenol procedure in adolescents with pilonidal sinus, focusing on success rates, recurrence, and complications.Material and methodTotal number of 28 adolescent patients with non-complicated PSD were included in this retrospective study.ResultsThis study included 28 adolescent patients (mean age: 15.04 ± 1.40 years), of which 60.7% were female. A total of 46.4% of the patients presented with a single sinus opening, while 53.6% had multiple sinus openings. Phenol procedure was administered with a mean of 3.32 ± 1.49 courses, resulting in complete healing in 75.0% of patients and an overall success rate of 82.1% after pre- or post-surgical procedure. Complications were observed in 14.3% of cases, while recurrence occurred in 21.4%. Persistent discharge was reported in 7.1% of patients, necessitating surgical excision.ConclusionsOur findings support that phenol treatment is a safe and effective minimally invasive approach for managing pilonidal sinus, demonstrating success rates comparable to conventional surgical methods. Furthermore, phenol procedure offers notable advantages, including preservation of tissue integrity, ease of implementation, and reduced recovery times, rendering it particularly advantageous for adolescent patients.